Vectors: recognising the challenge and reducing neglect. Issue 5 (1st January 2019) - Hemingway, Janet
Abstract: Vector control is essential for the prevention and reduction of malaria transmission and is increasingly recognised as a key element of several neglected tropical disease (NTD) elimination programmes. Very few vector control interventions have a strong evidence base for their public health impact, and those that do are insecticide-based and threatened by resistance. The pipeline of new interventions and new insecticides is being filled and several are undergoing randomised controlled trials. If these are subsequently to be used sustainably, interventions will need to be combined. The major challenge will be to generate the evidence base and funding to achieve this sustainable combination at the country level. Unless this is done, the selection pressure for resistance to the new generation of vector control tools is likely to rapidly reduce our ability to control insect vectors in the foreseeable future.